2021
DOI: 10.3390/nu13113980
|View full text |Cite
|
Sign up to set email alerts
|

Acute Paraxanthine Ingestion Improves Cognition and Short-Term Memory and Helps Sustain Attention in a Double-Blind, Placebo-Controlled, Crossover Trial

Abstract: This study examined the effects of acute paraxanthine (PXN) ingestion on markers of cognition, executive function, and psychomotor vigilance. In a randomized, double blind, placebo-controlled, crossover, and counterbalanced manner, 13 healthy male and female participants were randomly assigned to consume a placebo (PLA) or 200 mg of PXN (ENFINITY™, Ingenious Ingredients, L.P.). Participants completed stimulant sensitivity and side effect questionnaires and then performed the Berg Wisconsin Card Sorting Test (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…The Go/No-Go test was used to assess the ability to sustain attention, control responses to visual stimulation, reaction time, and accuracy [29,30,33]. We previously reported that acute ingestion of 200 mg of PXN decreased mean response time to Go Tasks while response time increased over time with PLA treatment [25]. We observed a similar response to 100 mg and 200 mg dosages in the present study, but not 50 mg dosage.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…The Go/No-Go test was used to assess the ability to sustain attention, control responses to visual stimulation, reaction time, and accuracy [29,30,33]. We previously reported that acute ingestion of 200 mg of PXN decreased mean response time to Go Tasks while response time increased over time with PLA treatment [25]. We observed a similar response to 100 mg and 200 mg dosages in the present study, but not 50 mg dosage.…”
Section: Discussionsupporting
confidence: 78%
“…The Sternberg Task Test assesses reaction time, accuracy, and memory of tasks of increasing complexity [34,[50][51][52]. In our initial study, we found ingestion of 200 mg of PXN improved reaction time more consistently than the PLA in shorter (2-letter) and longer (6-letter) memory challenges [25]. There was also evidence that reaction time improved more consistently over time as the number of trials progressed.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations